The Baltic Germans and the parliamentary Republic of Latvia: Higher education context - Rubenis, Rūdolfs (Przegląd Środkowo-Wschodni, 2023)
The aim of the article is to evaluate the role of the Baltic Germans in the higher education system of Latvia during the interwar period in the parliamentary Republic of Latvia, paying attention also to the role of the national ideology of the Latvian state in the University of Latvia (UL). The Baltic Germans are a specific and unique ethnic group in the history of the Baltic region, without whom today’s Latvian higher education would not be possible. Latvian higher education began with the German founded Riga Polytechnikum/Riga Polytechnical institute (RP/RPI) in 1862, which in the first half of the 1920s was transformed into the UL, where higher education in Latvian first began. However, due to the legacy of the RP/RPI, German and Russian academical languages were retained as well as the Latvian academical language. The article is based on the Documents of the Latvian State Historical Archives of Latvian National archive (LNA LVVA) and the Museum of the University of Latvia, the existing historiography of Baltic Germans history problems, structured around the following issues: Origins of higher education in Latvia; the establishment of the University of Latvia: benefit or loss for the Baltic Germans; the attitude of the Latvian state towards Baltic Germans in higher education.